2015
DOI: 10.11648/j.ijgg.20150305.11
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational Genetic Effect of Trichloroethane (TCE) on Phenotypic Variation of Acrosomal Proteolytic Enzyme and Male Infertility Risk

Abstract: Exposure to trichloroethane (TCE), a ambiguous environmental toxicant, has been negatively associated with male reproductive performance. The objective was to investigate, in-vivo, the mutagenic, carcinogenic or teratogenic effect of TCE maternal exposure on sperm quality and testicular cytoarchitecture of F1 generation of mice. A motile sperm separation technique was used to estimate sperm motility and a gelatin slide technique was used to measure the number of the halo around the acrosome of individual sperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Many studies reported that exposure to environmental insults may promote the transition of abnormal phenotypes between generations (Jones et al, 1996;Anway et al, 2005). The results of this study support our findings from previous studies in mice (Al-Griw et al, 2015b) by examining a variety of different abnormalities states in four-month-old male mice and characterizing the transgenerational changes in the F1 generation sperms (Al-Griw et al, 2015a). Early exposure to TCE reduces fertility and negatively affects pregnancy outcomes across multiple generations (AlGriw et al, 2015c).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Many studies reported that exposure to environmental insults may promote the transition of abnormal phenotypes between generations (Jones et al, 1996;Anway et al, 2005). The results of this study support our findings from previous studies in mice (Al-Griw et al, 2015b) by examining a variety of different abnormalities states in four-month-old male mice and characterizing the transgenerational changes in the F1 generation sperms (Al-Griw et al, 2015a). Early exposure to TCE reduces fertility and negatively affects pregnancy outcomes across multiple generations (AlGriw et al, 2015c).…”
Section: Discussionsupporting
confidence: 90%
“…Experimental studies in rodents indicate that exposure to environmental toxic substances during intrauterine life, postnatal life, early life, and/or germ cell exposures play a significant role in determining the mature phenotype and susceptibility to diseases in later life (Skinner et al, 2010(Skinner et al, , 2013. Epigenetic abnormalities/diseases in humans have been documented for reproductive tract abnormalities, brain and behavior abnormalities, immune system abnormalities (Anway et al, 2006a;Crews et al, 2007) as well as kidney (Anway et al, 2006b), ovarian, testis and prostate diseases (Salian et al, 2009;Nilsson et al, 2012;Al-Griw et al, 2015a). A number of environmental factors have been shown to induce transgenerational inheritance of adult onset disease and phenotypic variations (Skinner et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the role of lipid peroxidation in TCE-induced toxicity, the serum levels of MDA in mice treated with TCE were determined (Figure 4). Lipid peroxidation (malondialdehyde; MDA) is a marker of oxidative lipid damage and a major oxidative product of peroxidized polyunsaturated fatty acids [19]. The results showed that serum MDA levels were significantly increased in the TCE-treated mice when compared with those in controls, with the highest levels recorded in the 400 µg/kg TCE-treated mice ( Figure 4A).…”
Section: Tce Increases Lipid Peroxidation In the Serummentioning
confidence: 99%
“…Then, 4 ml n-butanol was added, and the solution was centrifuged, cooled and the absorption of supernatant was obtained using spectrophotometer at 532 nm. The calibration curve was obtained using different concentrations of 1, 1, 3, 3-tetramethoxypropane as standard to determine the concentration of TBARS in samples as nmol/ml [18][19].…”
Section: Estimation Of Tbars In the Seramentioning
confidence: 99%